GREEN EDUCATION GUNA MENUMBUHKAN JIWA WIRAUSAHA SEJAK DINIBERBASIS BUSINESS MODEL CANVAS DI SEKOLAH ALTERNATIF “TEMBASALEKO”KOTABIMA - APRIANTI, KARTIN; PRATIWI, ALIAH; MULYATI, MULYATI; SULISTIANINGSIH, SULISTIANINGSIH; ANANTA, ASTI (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
The partner of this community empowerment program for beginners (PMP) is the alternative school “Temba Saleko”. In addition to the main learning activities, the alternative school “Temba Saleko” is committed to developing children into creative and innovative individuals while still paying attention to environmental preservation. Based on the results of field visits and interviews, several problems faced by partners related to their students can be identified, namely: a) children's awareness and knowledge of environmental preservation is still low; b) low interest in entrepreneurship; and c) limited human resources who understand the business model canvas as a tool for developing creative ideas. The objectives and targets of this PMP are: a) fostering a proactive and adaptive attitude towards environmental problems; b) instilling and fostering an entrepreneurial spirit from an early age that supports green education and green economy; and c) making the business model canvas a tool for expressing creative ideas. Through the PMP grant program, the PMP team together with partners carry out various activities, including green education socialization, educational visits to the Main Waste Bank of Bima City, entrepreneurship seminars, and business model canvas training aimed at instilling an entrepreneurial spirit that supports green education and green economy from an early age. Based on the evaluation results, the PMP program showed an increase of 91.7% in knowledge, attitudes, and skills, and 97.9% of participants strongly agreed with the positive impact of the activities that had been implemented. From the activities that had been implemented, the PMP team produced several program products, including crafts from used plastic bottles, green education e-modules, waste sorting project e-modules, Kidspreneur green entrepreneurship e-modules, Kidspreneur-Project Model Canvas e-modules My Business, animated video "Entrepreneurial Inspiration", and animated video "My Trash, My Creation". ABSTRAKMitra program pemberdayaan masyarakat pemula (PMP) ini adalah sekolah alternatif “Temba Saleko”. Selain kegiatan utama pembelajaran, sekolah alternatif “Temba Saleko” berkomitmen untuk mengembangkan anak-anak menjadi individu kreatif dan inovatif dengan tetap memperhatikan pelestarian lingkungan hidup. Berdasarkan hasil kunjungan lapangan dan wawancara, beberapa permasalahan yang dihadapi mitra terkait peserta didiknya dapat diidentifikasi, yaitu: a) kesadaran dan pengetahuan anak-anak tentang pelestarian lingkungan hidup masih rendah; b) rendahnya minat berwirausaha; dan c) keterbatasan sumber daya manusia yang memahami business model canvas sebagai alat untuk mengembangkan ide kreatif. Tujuan dan target dari PMP ini adalah: a) menumbuhkan sikap proaktif dan adaptif terhadap masalah lingkungan; b) menanamkan dan menumbuhkan jiwa wirausaha sejak dini yang mendukung green education dan green economy; serta c) menjadikan business model canvas sebagai alat untuk mengekspresikan ide-ide kreatif. Melalui program hibah PMP, tim PMP bersama mitra melaksanakan berbagai kegiatan, antara lain sosialisasi green education, kunjungan edukatif ke Bank Sampah Induk Kota Bima, seminar kewirausahaan, dan pelatihan business model canvas yang bertujuan menanamkan jiwa wirausaha yang mendukung green education dan green economy sejak dini. Berdasarkan hasil evaluasi, program PMP menunjukkan peningkatan sebesar 91,7% dalam pengetahuan, sikap, dan keterampilan, serta 97,9% peserta kegiatan sangat menyetujui dampak positif dari kegiatan yang telah dilaksanakan. Dari kegiatan yang telah dilaksanakan, tim PMP menghasilkan beberapa produk program, antara lain kerajinan dari botol plastik bekas, e-modul pendidikan hijau, e-modul proyek memilah sampah, e-modul Kidspreneur kewirausahaan hijau, e-modul Kidspreneur-Project Model Canvas Bisnisku, video animasi "Inspirasi Wirausaha", dan video animasi "Sampahku, Kreasiku".